If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3b + 6) = 2(6b + -22) Reorder the terms: 6(6 + 3b) = 2(6b + -22) (6 * 6 + 3b * 6) = 2(6b + -22) (36 + 18b) = 2(6b + -22) Reorder the terms: 36 + 18b = 2(-22 + 6b) 36 + 18b = (-22 * 2 + 6b * 2) 36 + 18b = (-44 + 12b) Solving 36 + 18b = -44 + 12b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-12b' to each side of the equation. 36 + 18b + -12b = -44 + 12b + -12b Combine like terms: 18b + -12b = 6b 36 + 6b = -44 + 12b + -12b Combine like terms: 12b + -12b = 0 36 + 6b = -44 + 0 36 + 6b = -44 Add '-36' to each side of the equation. 36 + -36 + 6b = -44 + -36 Combine like terms: 36 + -36 = 0 0 + 6b = -44 + -36 6b = -44 + -36 Combine like terms: -44 + -36 = -80 6b = -80 Divide each side by '6'. b = -13.33333333 Simplifying b = -13.33333333
| A=1/2(6+3)3 | | 8a-2b=11 | | 5(2x-1)+3x=2(x+5) | | A=1/2(6+3) | | x^2+4x^2-25=2x^2 | | y=2x^2-8x-4 | | A=1/2(4+3)2 | | d+(2d-3)=13(d-1) | | A=1/2(10+7)4 | | 4.9q-5.1-5.3q=-1.4q-4.8 | | -45m+68=84m | | 9x+6=7+18 | | 6x+5x+4+9=8x+4+2x | | 3n+2(n+4)=56 | | 111=79 | | 5.7q-1.3-5.6q=0.9q-3.4 | | -54-8v=-7v+21 | | x^2-2x=-5 | | -x+5=-8x+6 | | -4x-2(-5x-1)=-6.5+2(10-x) | | 4-(5-7x)=2(x+1) | | M-27=-46 | | (2a+3b+4c)+(4a+2b)= | | 2u=10 | | 7=t+6 | | 7 = t + 6 | | X(x-4)(x+7)(2x-9)=0 | | 9x=-8y+72 | | 3(7+x)=24 | | 7x+5=21 | | 3x^3-24x^2+36x=0 | | 11k-8k-3=9 |